Characterisation of a conserved motif found within the Dlx cis-regulatory element URE2 and its effect on mouse URE2-lacZ activity in transgenic mice - Lavoie, Monique V (University of Ottawa (Canada), 2010)
The Distal-less-like genes, commonly referred to as Dlx genes, encode homeodomain transcription factors essential for the establishment of GABAergic interneurons in the ventral forebrain as well as their migration to the cortex. The cis-regulatory element URE2 (enhancer) is located upstream of Dlx1 and is thought to regulate the transcription of Dlx1 and/or Dlx2. The objective of this study was to examine a short conserved sequence within the URE2 element, corresponding to nucleotides 699-719, and to evaluate its contribution to URE2 activity in transgenic mouse forebrain. My results showed that a mutant version of the URE2 element, in which nucleotides 699-719 were modified, was active in the cortex and the ventricular zone of forebrain of the transgenic mice produced with the mutant enhancer, where Dlx1/Dlx2 are not usually expressed. This indicated a loss of binding by a protein with a transcriptional repressor function. Previous analyses suggested that mURE2nt699-719 would be a good candidate for a REST repressor binding site. However, we were not able to observe any transcriptional regulation by REST in co-transfection experiments performed in cultured cells. This, as well as revised bioinformatical information, led us to identify four new candidates possibly using mURE2nt699-719 as a binding site, namely the Nuclear- Factor-1 proteins: NFIA, NFIB, NFIC and NFIX. These genes are associated with transcriptional regulation, being repressors and/or activators of gene expression in the brain. We showed that NFIC was able to utilize the mURE2nt699-719 sequence to reduce the luciferase reporter expression in neuronal cells, which would explain the loss of repression in our transgenic mice at embryonic days E11.5 and E13.5. These preliminary results also allowed us to suggest that a heterodimer between NFIC/NFIB and NFIC/NFIX binds to the mURE2699-719 sequence at embryonic day E15.5 and postnatal day 0 (P0) of the transgenic mice since the mutated enhancer's activity seems to indicate a loss of an activator at those stages. These results suggest that these factors could possibly be required for the regulation of the Dlx genes by URE2. These results will also help clarify the role of URE2 by identifying transcription factors that contribute to the genetic program involved in the cellular organization of the developing forebrain in vertebrates.
Keywords: Biology, Genetics.